Acute responses to 10×15 m repeated sprint ability exercise in adolescent athletes: the role of change of direction and sport specialization - Nikolaidis, P. T.; Meletakos, P.; Tasiopoulos, I.; Kostoulas, I.; Ganavias, P. (Asian Journal of Sports Medicine, 2016)
Background: The repeated sprint ability (RSA) has been studied with protocols using distances longer than 20 m per sprint, whereas basketball players cover on average less than 20-meter distance per sprint during match..